Ectopic Lipid Accumulation and Reduced Glucose Tolerance in Elderly Adults Are Accompanied by Altered Skeletal Muscle Mitochondrial Activity - Johannsen, Darcy L.; Conley, Kevin E.; Bajpeyi, Sudip; Punyanitya, Mark; Gallagher, Dympna; Zhang, Zhengyu; Covington, Jeffrey; Smith, Steven R.; Ravussin, Eric (The journal of clinical endocrinology and metabolism, 2012)
Context:Aging is associated with insulin resistance and unfavorable changes in body composition including increased fat accumulation, particularly in visceral and ectopic depots. Recent studies suggest that skeletal muscle mitochondrial activity may underlie some age-associated metabolic abnormalities.Objective:Our objective was to measure mitochondrial capacity and coupling of the vastus lateralis muscle in elderly and young adults using novel in vivo approaches and relate mitochondrial activity to metabolic characteristics.Design:This was a cross-sectional study.Participants and Intervention:Fourteen sedentary young (seven males and seven females, 20–34 yr of age) and 15 sedentary elderly (seven males and eight females, 70–84 yr of age) nonobese subjects selected for similar body weight underwent measures of body composition by magnetic resonance imaging and dual-energy x-ray absorptiometry, oral glucose tolerance, and in vivo mitochondrial activity by 31P magnetic resonance and optical spectroscopy. Muscle biopsy was carried out in the same muscle to measure mitochondrial content, antioxidant activity, fiber type, and markers of mitochondrial biogenesis.Results:Elderly volunteers had reduced mitochondrial capacity (P = 0.05) and a trend for decreased coupling efficiency (P = 0.08) despite similar mitochondrial content and fiber type distribution. This was accompanied by greater whole-body oxidative stress (P = 0.007), less skeletal muscle mass (P < 0.001), more adipose tissue in all depots (P ≤ 0.002) except intramyocellular (P = 0.72), and lower glucose tolerance (P = 0.07).Conclusions:Elderly adults show evidence of altered mitochondrial activity along with increased adiposity, oxidative stress, and reduced glucose tolerance, independent of obesity. We propose that mild uncoupling may be induced secondary to age-associated oxidative stress as a mechanism to dissipate the proton-motive force and protect against further reactive oxygen species production and damage.